Pain perception and coping strategies influence early outcomes following knee surgery in athletes. Issue 1 (January 2020) - Everhart, Joshua S.; Chafitz, Aaron J.; Harris, Kristie M.; Schiele, Steven E.; Emery, Charles F.; Flanigan, David C.
Abstract: Objectives: To determine whether pain perceptions and coping strategies are predictive of the following outcomes after knee surgery in athletes: (1) return to similar level of sport, (2) improvement in symptoms, and (3) improvement in kinesiophobia. Design: Prospective cohort study. Methods: 101 athletes (52 men, 49 women; mean age 32.7 years) at mean 12.1 months follow-up were included. Independent relationships between patient outcomes and pre-operative measures were determined: short form McGill Pain questionnaire (SF-MPQ), Pain Catastrophizing Scale (PCS), Pain Coping Measure (PCM), and the brief COPE subscales of acceptance, denial, positive reframing, and use of instrumental support. Adjustment was performed for length of follow-up, symptom duration, surgical history, age, activity level, and surgical procedure. Results: Rate of return to similar level of sport was 73%; severe pain catastrophizers (PCS >36 points) had increased odds of not returning to similar level of sport (OR 11.3 CI 1.51, 236; p = 0.02) whereas COPE-use of instrumental support was protective (per point increase: 0.72 CI 0.54, 0.94; p = 0.02). Problem-focused coping positively correlated with improvement in IKDC-S scores (beta 0.032 SE 0.010; p = 0.001). Improvement in kinesiophobia after surgery was less likely with higher pre-operative perceived pain frequency (OR 0.23 CI 0.06, 0.71; p = 0.009) and higher COPE-denial scores (OR 0.43 CI 0.21, 0.88; p = 0.02). Conclusions: Among athletes undergoing knee surgery, severe pain catastrophizing is negatively associated with return to similar level of sport. Instrumental support and problem-focused coping strategies are associated with improved outcomes. High preoperative pain scores are negatively associated with improvement in kinesiophobia after rehabilitation.